1282. Safety, Tolerability, and Pharmacokinetics of BRII-732, A Medoxomil Carbonate Prodrug of Islatravir in Healthy Adult Subjects. (15th December 2022) - Margolis, David A; Ma, Ji; Watkins, Michael; Wang, Yujin; Trivedi, Chetana; Peng, Chi-Chi; Wei, Xuelian; Zhong, Lijie; Patel, Kamlesh; Girardet, Jean-Luc; Wang, Michael; VonderEmbse, Annalise; et al.
Abstract: Background: BRII-732, a prodrug of islatravir (ISL), is a potent HIV-1 nucleotide reverse transcriptase translocation inhibitor. Following oral absorption, BRII-732 is rapidly converted to ISL, which is metabolized intracellularly to the active metabolite, ISL triphosphate (ISL-TP). Single doses of ISL as low as 0.5 mg significantly suppressed HIV-1 RNA by more than 1.0 log at day 7 in treatment-naive adults with HIV-1 infection. Current development work with BRII-732 is designed to provide optimal drug exposure to enable once weekly (QW) dosing, to be part of combination antiretroviral therapy to provide improved patient convenience and treatment adherence. Methods: This was a Phase 1, randomized, double-blind, placebo-controlled study consisting of healthy adult subjects enrolled in five single ascending dose and two multiple ascending dose cohorts. The objectives of the study were to assess the safety, tolerability, and PK profiles of BRII-732 and ISL in plasma; ISL-DP and ISL-TP in human PBMCs. BRII-732 was orally administered in the fasted state using an oral solution formulation. Safety-related assessments included physical examinations, ECGs, vital signs, AEs, and standard clinical laboratory tests. Results: BRII-732 as single dose or multiple doses was generally safe and well-tolerated when administered to healthy adult subjects. There were no Grade ≥ 3 AEs, SAEs, drug-related AEs leading to withdrawal or graded lymphocyte abnormalities. BRII-732 rapidly converted to ISL post BRII-732 oral administration with no detectable level (LLOQ = 1.0 ng/mL) of BRII-732 in systemic circulation at 0.5h. Dose proportional ISL exposure increases were observed over the dose range of 10 mg to 200 mg of BRII-732. No meaningful ISL accumulation in plasma was observed after 3 QW BRII-732 doses. ISL-DP and ISL-TP exposures in PBMC cells increased dose-dependently. Approximately 1.7-2.0 fold accumulation ratios for ISL-DP and ISL-TP are consistent with observed long terminal half-lives of 110-150 hours. Conclusion: Safety, tolerability and PK profiles including ISL in plasma and ISL-TP in PBMC cells after single and multiple oral administrations of BRII-732 supports further development of BRII-732 as part of oral weekly combination antiretroviral therapy. Disclosures: David A. Margolis, MD MPH, Brii Biosciences: Stocks/Bonds Ji Ma, PhD, Brii Biosciences: Stocks/Bonds Michael Watkins, PharmD, Brii Biosciences: Stocks/Bonds Yujin Wang, M.Sc., Brii Biosciences: Stocks/Bonds Chetana Trivedi, B.A., Brii Biosciences: Stocks/Bonds Chi-Chi Peng, PhD, Brii Biosciences: Stocks/Bonds Xuelian Wei, PhD, Brii Biosciences: Stocks/Bonds Lijie Zhong, PhD, Brii Biosciences: Stocks/Bonds Kamlesh Patel, PhD, Brii Biosciences: Stocks/Bonds Jean-Luc Girardet, PhD, Brii Biosciences: Stocks/Bonds Michael Wang, PhD MBA, Brii Biosciences: Stocks/Bonds Annalise VonderEmbse, PhD, Brii Biosciences: Stocks/Bonds Li Yan, MD PhD, Brii Biosciences: Stocks/Bonds Zhi Hong, PhD, Brii Biosciences: Ownership Interest Lianhong Xu, PhD, Brii Biosciences: Stocks/Bonds.